Sistem Pendukung Keputusan Penilaian Dosen Terbaik Menggunakan Metode Analytical Hierarchy Process (AHP) Studi Kasus Fakultas Keguruan dan Ilmu Pendidikan Universitas Dehasen Bengkulu - Magdalena Sundari; Asnawati Asnawati; Indra Kanedi (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2024)
The AHP method used in this decision support system can help decision makers in solving complex problems by considering existing criteria and sub-criteria. It is hoped that this decision support system will make it easier for the faculty to assess lecturer performance objectively and effectively so that it can improve the quality of education at Dehasen University, Bengkulu. Waterfal method, ready-made software that is operated by the user and carried out maintenance. Maintenance allows developers to make corrections to errors that were not detected in previous stages. Maintenance includes repairing errors. Based on the research that has been carried out through the stages of analysis, design, system development, system testing and implementation, it can be concluded that, the system built using the Analytical Hierarchy Process (AHP) method in selecting the best lecturers can provide information in the form of the best lecturers in accordance with the criteria and also the conditions that the user enters, the Analytical Hierarchy Process (AHP) method uses input in the form of assessments for each criterion that can run well according to the design, the decision support system uses the analytical hierarchy process (AHP) method where the value obtained is a consistent value if the value of CR is equal to or more than 0.1 (10%).